2021
DOI: 10.1111/nan.12749
|View full text |Cite
|
Sign up to set email alerts
|

Splicing factor proline and glutamine rich intron retention, reduced expression and aggregate formation are pathological features of amyotrophic lateral sclerosis

Abstract: Aim Splicing factor proline and glutamine rich (SFPQ) is an RNA–DNA binding protein that is dysregulated in Alzheimer's disease and frontotemporal dementia. Dysregulation of SFPQ, specifically increased intron retention and nuclear depletion, has been linked to several genetic subtypes of amyotrophic lateral sclerosis (ALS), suggesting that SFPQ pathology may be a common feature of this heterogeneous disease. Our study aimed to investigate this hypothesis by providing the first comprehensive assessment of SFPQ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…In light of our findings, we propose that perturbed control of intron retention in ALS includes the formation of pathogenic PreT-IR transcripts induced by loss of SFPQ function in both the nucleus and neurites, and that this misregulation impacts patients’ neurites most severely. Supporting this model, we found that the intron retention signature shared across ALS studies is also present in zebrafish null neurons 18 , 19 , 33 , 34 . Loss of SFPQ function likely perturbs the splicing of SFPQ-binding introns.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In light of our findings, we propose that perturbed control of intron retention in ALS includes the formation of pathogenic PreT-IR transcripts induced by loss of SFPQ function in both the nucleus and neurites, and that this misregulation impacts patients’ neurites most severely. Supporting this model, we found that the intron retention signature shared across ALS studies is also present in zebrafish null neurons 18 , 19 , 33 , 34 . Loss of SFPQ function likely perturbs the splicing of SFPQ-binding introns.…”
Section: Discussionsupporting
confidence: 67%
“…An emerging hallmark of ALS/FTLD, increased retention of specific introns in spliced mRNAs, has been observed across a range of genetic backgrounds, in cellular and animal models and patient tissue. Key affected introns are common across multiple datasets 18 , 19 , 33 , 34 . A functional connection between SFPQ misregulation and aberrant intron retention in ALS/FTLD has not yet been explored.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mislocalization and cytoplasmic aggregation of nuclear SFPQ are associated with the pathogenesis of ALS [4][5][6]. We have previously demonstrated that the application of ZnCl 2 enhances the cytoplasmic accumulation and aggregation of SFPQ when overexpressed in cultured neurons [12].…”
Section: Fals-associated N533h and L534i Mutants Promote Sfpq Cytopla...mentioning
confidence: 99%
“…These RBPs are best exemplified by trans-activation response element DNA-binding protein 43 (TDP-43) and fused in sarcoma (FUS), both of which predominantly function in the nucleus under normal conditions but are mislocalized and aggregated in the disease state [2,3]. Recent evidence has also demonstrated abnormal cytoplasmic accumulation and loss of the nuclear pool of an RBP, splicing factor prolineand glutamine-rich (SFPQ) protein, in ALS [4][5][6]. However, the precise molecular mechanisms that underpin these pathological changes, and their effects on neuronal functions are not well understood.…”
Section: Introductionmentioning
confidence: 99%